Pemanfaatan Sampah Plastik Gelas Air Mineral Sebagai Alat Peraga Pembelajaran Sosiologi - Andhy Surya Hapsara (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2025)
The aim of this study was to improve learning outcomes on sociology subject, and also to provoke student’s motivation and creativity on social structure competence by asked them to create study model made from mineral water plastic waste as learning method. This study taken place on 11th grade of social class in SMA N 1 Sedayu on 2015-2016 academic year. This study used classroom action research design in 2 cycles. The result of this study showed that there were improvement of student’s mark from 77,30 in first cycle to 81,09 in second cycle. The learning method pursued student to analyze the real model of social structure which consist of social diferentiation and social stratification. Meanwhile the study model describe that intersection will form social integration, consolidation provoke social conflict, whilst social stratification pyramid model describe that real social stratification have close and open characteristic. It can be conclude from this study that creating study model made from mineral water plastic waste could be applied on sociology learning procces, especially on intereaction patern of social diferentiation and social stratification pyramid topics in social structure competence.